Dapagliflozin: a potential lifesaver for “heart failure patients with mildly reduced or preserved ejection fraction” in the world - Bijarani, Faizan Shafqat Ali; Nazeer, Ahsan; Bisma Shaikh (Journal of the Pakistan Medical Association, 2023)
Dear Editor, According to the "World Health Organization (WHO)," approximately 17.9 million people die each year from cardiovascular diseases like heart failure, making it the second-leading cause of death in the world after cancer. (1) Consequently, treatment and care for heart failure patients have been significant concerns among medical professionals for years. Despite the numbers, Pakistan still lacks the primary resources to support heart failure patients. According to the data on the heart attack ratio for 2020, approximately 240,720 people died from heart failure and coronary artery disease (CAD) in Pakistan, accounting for around 16 percent of all fatalities. (2) However, Dapagliflozin, a sodium-glucose transporter inhibitor (SGLTi), along with a healthy diet, exercise, and other medications, improves glycemic control in adults with type 2 diabetes and also reduces the risk of hospitalization for heart failure among adults with type 2 diabetes.(3) In a study published in JAMA Cardiology in 2023, Jhund PS et al. examined the relationship between Dapagliflozin and heart failure and discovered a reduction of the rate of total HF events in patients with mildly reduced or preserved ejection fraction and cardiovascular deaths in the Dapagliflozin group by 3.5 events as compared to the placebo group. (4) Additionally, Scott Solomon et al. indicated that Dapagliflozin reduced the combined risk of worsening heart failure or cardiovascular death among patients with heart failure with reduced or preserved ejection fraction by 3.1% in the Dapagliflozin group as compared to the placebo group. (5) These satisfying statistics indicate that Dapagliflozin is the world’s potential lifesaver for heart failure patients with mildly reduced or preserved ejection fraction. In order to ensure the safety of heart failure patients, it is imperative to promote and scale up the research, production, and availability of the drug Dapagliflozin in our healthcare systems and pharmacies on a large scale in Pakistan, particularly in rural and remote areas.